A novel germline MLH1 mutation causing Lynch Syndrome in patients from the Republic of Macedonia - Hiljadnikova-Bajro, Marija; Josifovski, Toni; Panovski, Milco; Dimovski, Aleksandar J (My University, 2012)
To implement molecular analysis in the clinical diagnosis and management of Lynch syndrome (LS).
Keywords: MLH1 mutation, Lynch Syndrome